PROSES NEWS BULETIN DAN MANAJEMEN STRATEGIS PROGRAM SIARAN BERITA SULTENG HARI INI DI LPP TVRI PALU: (Studi Deskriptif pada LPP TVRI Palu Sulawesi Tengah) - Pandewa, Bahauddin (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
LPP TVRI Sulteng, carries out activities in terms of publishing news, carrying out several stages starting from searching for news until the news is suitable for publication so that the implementation of activities is the News bulletin process and strategic management of the news broadcast program at today's Central Sulawesi event. Several stages are required to be carried out by journalists. Firstly, editorial meetings, secondly, reporting and making news, thirdly, the editing process, fourthly, making inserts, fifthly preparing the news, sixthly, broadcasting. From the six initial stages above, it will be supported by how LPP TVRI Palu employees carry out strategic management carried out by parties or program and business development divisions by going through (4) stages in carrying out strategic management, namely planning by holding meetings to choose the name of the program, promoting the program. broadcast by collaborating with other parties. Broadcast Production, publish reliable information, and carry out news rundowns. Program Execution, in this section it can be seen that the Central Sulawesi Today program is broadcast every day at 17:00 WITA by looking at the rest time from the daily activities of the people of Central Sulawesia. The final stage is the Monitoring and Evaluation section, the parts that will be monitored and evaluated are all the news that will be published. The supporting factors are having quite good and numerous human resources, dynamic broadcast programs and factual news to be published to the people of Central Sulawesi. However, there are several inhibiting factors, namely the coverage of the Central Sulawesi area which is wide enough for a reporter to cover an incident to make it into news, so that the existing news cannot be published directly to the public.